Top Ethical Issues Concerning Healthcare Providers Working in Saudi Arabia - Amar Mansour Almoallem; Mohammed Abdulaziz Almudayfir; Yassar H. Al-Jahdail; Anwar E. Ahmed; Adnan Al-Shaikh; Salim Baharoon; Abdullah AlHarbi; Hamdan Al-Jahdali (Springer, 2020)
Background: Healthcare providers working in Saudi Arabia come from various nationalities, cultures, and training backgrounds. This study aimed to assess the perceptions of healthcare providers working in Riyadh hospitals about ethical dilemmas and solutions. Methods: This is a cross-sectional study among physicians working in Riyadh's private and governmental hospitals between June and December 2017. The study collected information on demographics, knowledge about medical ethics, the sources of such knowledge, and common ethical issues in general and the top ethical issues and dilemmas encountered in their daily practice. Results: A total of 455 physicians from government and private hospitals were enrolled in the study. The mean age of the participants was 34.29 ± 10.5 years, females were 29.7% and mean years of practice was 13.0 ± 11.5. The top ethical issues identified by the participants were "disagreement with the patients' relatives about treatment" (91%), patient disagreement with decisions made by professionals (84%), treating the incompetent patient (79%), conflict with administration policy and procedures (77%), scarcity of resources (72%), and making decision about do-not-resuscitate or life-sustaining treatment (68%). There were significant differences in dealing with ethical issues in relation to gender, confidence about ethical knowledge, nationality, seniority, training site, and private or government hospitals academic and nonacademic. Conclusion: Healthcare providers in Riyadh hospitals face multiple ethical challenges. In addition to improvement in ethics knowledge through educational program among healthcare professional, there is a valid need for healthcare professionals and other sectors within society to engage in serious and continuous dialogue to address these issues and propose recommendations.